Back Cover: Supramolecular Wiring of Benzo‐1, 3‐chalcogenazoles through Programmed Chalcogen Bonding Interactions (Chem. Eur. J. 16/2016). Issue 16 (11th February 2016) - Kremer, Adrian; Fermi, Andrea; Biot, Nicolas; Wouters, Johan; Bonifazi, Davide
Abstract : A rational and convenient synthetic route for the preparation of stable 2‐substituted benzo‐1, 3‐chalcogenazoles is presented. The electron‐depleted σ‐holes on the chalcogen atoms are exploited to trigger programmed two‐ (X⋅⋅⋅Y) or three‐atoms (X⋅⋅⋅Y⋅⋅⋅X) supramolecular interactions in the solid state; this gives wirelike structures in the presence of suitable N‐containing ligands. More information can be found in the Full Paper by D. Bonifazi, et al. onpage 5665 ff.